Self-adaptive control of a bluff body wake by means of porous flaps. (1st January 2013) - Feuvrier, A.; Mazellier, N.; Kourta, A.
The effects resulting from the use of an innovating self-adaptive passive control system are investigated. The system studied here, is constituted of a couple of hinged porous flaps positioned symmetrically on each side of a bluff body. Its originality consists on its design which relies on a biomimetic approach, as well as its ability to self-adapt to the flow conditions. The comparison between the results obtain for the controlled model and the uncontrolled one, over the range of Reynolds numbers 2.104 to 8.104, lead to an average mean drag reduction of 22%. An investigation of the mean pressure distribution in the near wake of the body confirmed that flow topology at large scale is strongly modified. This study focus on the attenuation of pressure fluctuations observed at the centre of the cylinder base. This parameter is considered a valid indicator of a strong reduction of the drag fluctuations.